Facing death : where culture, religion, and medicine meet - Spiro, Howard M. (Howard Marget), 1924-2012; Curnen, Mary G. McCrea; Wandel, Lee Palmer; Yale University. Program for Humanities in Medicine; Goethe-Institut Boston (New Haven : Yale University Press, 1996)
This is an important manual for those professionally involved with the dying, as well as a treatment & consolation for private readers. It brings together medical and humanities experts, to reflect on medical, cultural and religious responses to death.
Attending to dying : limitations of medical technology (a resident's perspective) / Eric L. Krakauer -- Before their time : a clinicians's reflections on death and AIDS / Peter A. Selwyn -- The doctor's role in death / Sherwin B. Nuland -- Thoughts on euthanasia and physician-assisted suicide / Alan B. Astrow -- Learning to care for the dying / Alan C. Mermann -- Thoughts on witnessing death / James D. Kenney -- The changing face of death in children / Diane M. Komp -- When children mourn a loved one / Morris A. Wessel -- The emergence of hospice care in the United States / Florence S. Wald -- Caring for those who die in old age / Joanne Lynn -- Living in the maelstrom / Alvin Novick -- An ars moriendi for our time : to live a fulfilled life ; to die a peaceful death / Arthur E. Imhof -- The art of dying in Hindu India / Sylvia Vatuk -- Reflections on mortality from a Jewish perspective / James E. Ponet -- Catholic theology's main thoughts on death / Harald Wagner -- The law of the spirits : Chinese popular beliefs / Valerie Hansen -- The meaning of death in Islam / Ira M. Lapidius -- From this world to the next : notes on death and dying in early America / John Demos -- Ars memoriandi : the NAMES Project AIDS Quilt / Peter S. Hawkins -- Bearing the spirit home / Frederick J. Streets -- Witnessing death versus framing death / William B. McCullough -- Conclusion : retrospect and prospect / William J. Bouwsma.
"Prepared under the auspices of the Program for Humanities in Medicine, Yale University School of Medicine and the Goethe-Institut, Boston."
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Terminally ill; Death -- Psychological aspects; Death -- Religious aspects; Death -- Moral and ethical aspects; Death; Medicine -- Religious aspects; Professional ethics; Terminal Care; Terminally Ill; Attitude to Death; Death; Religion and Medicine; Ethics, Professional; Malades en phase terminale; Mort -- Aspect psychologique; Mort -- Aspect religieux; Mort -- Aspect moral; Soins en phase terminale; Mort; Médecine -- Aspect religieux; Déontologie professionnelle; terminally ill; deaths; professional ethics; SELF-HELP -- Death, Grief, Bereavement; FAMILY & RELATIONSHIPS -- Death, Grief, Bereavement; Professional ethics; Medicine -- Religious aspects; Death; Death -- Moral and ethical aspects; Death -- Psychological aspects; Death -- Religious aspects; Terminally ill; Sterven; Sociologische aspecten; Stervensbegeleiding